Foreign market entry strategies and post-entry growth: Acquisitions vs greenfield investments - Tan, Danchi (Journal of International Business Studies, 2009)
We examine the relationship between the foreign market entry strategy and the subsequent growth of a subsidiary. We build upon the Penrose theory of firm growth, and on the organizational economics, international management, and foreign market entry strategy literatures. We hypothesize that the post-entry growth of acquisitions is positively associated with weak and codifiable interdependence within the multinational enterprise network, whereas the post-entry growth of greenfield investments is positively related to strong and complex interdependence. Empirical findings from a sample of Japanese subsidiaries in the US lend support to our argument.